Wuthering heights - Fiennes, Ralph; Binoche, Juliette; Kominsky, Peter; Bronte, Emily 1818-1848.; Paramount Pictures (Quezon City Viva Home Entertainment, 1995)
Heathcliff is a bedraggled boy who was brought to Wuthering Heights by a father of two lovable kids, Cathy and Hindley. Friendship flourishes between Heathcliff and Cathy. But the latter decides to marry a certain Edgar Linton and thus denies her destiny. Heathcliff is now on course for a terrible vengeance which seeks to destroy not only the present generation, but their heirs as well.
Originally released as a motion picture in 1939.
Based on the novel by Emily Bronte.
Released as VHS by Paramount Pictures in 1992.
"Viva Video and Jemah Television presents"--Container.
Summary from the cover.
Screenplay Anne Devlin.
Keywords: Man-woman relationships -- England -- Yorkshire -- Drama; Feature films; England -- Social life and customs -- 19th century -- Drama